PENGGUNAAN MEDIA SOSIAL SEBAGAI MEDIA KOMUNIKASI PEMERINTAH DAERAH ISTIMEWA YOGYAKARTA UNTUK PROMOSI WISATA - Akmalia Hermastuti; Dian Eka Rahmawati (Jurnal Ilmu Sosial dan Ilmu Politik)
Information and communication technology is increasingly developing, making social media an important medium for DIY tourism. The research aims to analyze the use of Instagram and Tiktok as communication media for the DIY Provincial government to promote tourism as one of the leading sectors of DIY Province to increase regional income. This research uses qualitative methods with data collection techniques of documentation and interviews. The data obtained were then analyzed using three stages of activities, namely data reduction, data presentation, and conclusion drawing. The results showed that communicators in this context, namely the DIY Provincial Tourism Office and the Communication and Information Office, convey messages in the form of content on the social media used, namely Instagram and Tiktok @visitingjogja to communicants, namely the community of Instagram and Tiktok application users to arouse someone's interest in visiting a tourist destination in DIY Province. From the results obtained, researchers complement existing research. Researchers say that the use of Instagram and Tiktok @visitingjogja can complement each other in increasing tourism promotion, so this use is very effective and has a significant effect on the tourism promotion strategy used by the government in DIY Province.